Epidemiology of herpes zoster and post-herpetic neuralgia in China: A nationwide population-based survey - Yiqi Xia; Xin Ye; Wenhui Zhu; Jinxu Ai; Yang Shen; Zhenyu Shi; Chengsen Cui; Yemin Yuan; Dawei Zhu; Ping He (International Journal of Infectious Diseases)
Objectives: Herpes zoster (HZ) and post-herpetic neuralgia (PHN) cause substantial burden worldwide, whereas China lacks nationwide statistics of HZ incidence. This study aims to provide national epidemiology profile for HZ and PHN in China. Methods: A nationwide population-based survey was conducted in China in 2024. We calculated the incidence of HZ and proportion of PHN among patients with HZ and identified risk factors through multivariate regression. Incidence trend, seasonality, and duration of zoster-associated pain and rash were also analyzed. Results: The study included 27,868 individuals and found an adjusted annual HZ incidence of 5.85 per 1000 person-years, which was associated with female sex, older age, urban residency, and chronic diseases. A total of 15.84% of them developed PHN, with females and older individuals at greater risk. The HZ incidence rose each year and increased largely after 2022. There was no seasonality trend of HZ or PHN. Around one-third of patients experienced zoster-associated pain for longer than 3 months and had the rash for more than weeks. Conclusion: This study establishes the first nationwide epidemiology profile of HZ in China, quantifies the proportion of PHN, and identifies key risk factors including female sex, older age, urban residency, and chronic comorbidities.